How could nanobiotechnology improve treatment outcomes of anti-TNF-α therapy in infammatory bowel disease? Current knowledge, future directions - Eder, Piotr (2021)
Despite significant advances in therapeutic possibilities for the treatment of inflammatory bowel disease (IBD) in recent years, there is still a big room for improvement. In particular, biological treatment can induce not only clinical remission but also mucosal healing of the gastrointestinal tract. Among these therapeutic molecules, anti-tumor necrosis factor-alpha (anti-TNF-$α$) antibodies were the first to revolutionize treatment algorithms in IBD. However, due to the parenteral route of administration and systemic mode of action, TNF-$α$ blockers are characterised by high rates of immunogenicity-related loss of response and serious adverse events. Moreover, intravenous or subcutaneous therapy is not considered patient-friendly and requires occasional, direct contact with healthcare centres. To overcome these limitations, several attempts have been made to design oral pharmaceutical formulations of these molecules. It is hypothesized that oral anti-TNF-$α$ antibodies therapy can directly provide a targeted and potent anti-inflammatory effect in the inflamed gastrointestinal tissues without significant systemic exposure, improving long-term treatment outcomes and safety. In this review, we discuss the current knowledge and future perspectives regarding different approaches made towards entering a new era of oral anti-TNF-$α$ therapy, namely, the tailoring of biocompatible nanoparticles with anti-TNF-$α$ antibodies for site-specific targeting to IBD. In particular, we discuss the latest concepts applying the achievements of nanotechnology-based drug design in this area.